So lets say we wanted to eliminate x if we added both of the equations together, hwo would you do that?
I knew I needed to eliminate a variable, I'm just not sure how to set up the equations together. 2(3y -1) + 2y=-6 ??? @Jhannybean
Thank you for your time btw
First try multiplying -2 to the entire first equation. -2(x + 3y = -1) 2x + 2y = 6 _____________________________ Now rewrite both equations after expanding the first one.
@Jhannybean I am having a difficult time
Okay let's start you off. multiplying 2 to each term within the parenthesis, you get: -2x - 6y = 2 2x + 2y = 6 ________________ Did you see what i did?
Ok yes! I know there is more to understand
I want to know how I solve the other one
The other one?
Is still don't have a full understanding! @Jhannybean I have to solve more problems like this And I want to be able to do it on my own
Have you finished solving this one?
No, I thought you were explaining the steps on how to solve it. So you got -2x-2y= 6 by multiplying 2 to each term. Idk what to do next or even where you got the number 2 :(
OK after the step i wrote above, you want to ADD the two equations together. -2x - 6y = 2 2x + 2y = 6 ___________________ 0x - 4y = 8 - 4y = 8 Divide both sides by -4 to isolate y, and you'll have your answer for the "y" portion
so -4 divided by -4?That equals 1
I am so confused @Jhannybean
yes thats correct,t hen what is 8/ -4 ?
I don't know the answer or the steps to get the answer. :( @Jhannybean
Okay, you're almost there!
Now that we have y, we can use this value to find x. Let's take the first equation for example. x + 3y = -1 If we use our value, y = -2, we can find x. x + 3(-2) = -1 x = -1 +6 x = ?
5!!!!!!!!!!!!!!!!!! Holy cow the answer is D (5,-2) Could you please help me with a similar question. I don't get how you got the negative two :) @Jhannybean
We got the -2 when we eliminated x to solve for y. Look at the above posts.